Carrageenan Edible Coating Application Prolongs Cavendish Banana Shelf Life - Fenny Martha Dwivany; Ayesha Nilam Aprilyandi; Veinardi Suendo; Nisrina Sukriandi (International Journal of Food Science)
Banana is very important for both food and economic securities in many tropical and subtropical countries, because of its nutritional values. However, banana fruit is a climacteric fruit which has short shelf life, so an alternative method to delay its ripening is needed. Our group has used carrageenan as an edible coating to delay banana fruit ripening. In this study, the effect of different concentrations of carrageenan and storage temperatures on Cavendish banana shelf life and fruit quality was evaluated. The fruits were treated with 0.5%, 1.0%, and 1.5% carrageenan and stored at two different temperatures, 26°C and 20°C. Carrageenan functional groups in banana peel samples as well as changes in surface structure of banana peel, color, weight loss, pulp to peel ratio, total soluble solid, and levels of MaACS1 and MaACO1 gene expression were analyzed. Result showed that the optimum condition to extend shelf life and maintain fruit quality was by treating the banana fruits with 1.5% carrageenan and storing them at a cool temperature (20°C). In addition, the result obtained from this study suggested that carrageenan can be used as edible coating to extend the shelf life of banana fruits (Musa acuminata AAA group).